Beef - Williams, Lee Ann (Open Mic: A Creative Writing Journal, 2025)
Lee-Ann Williams - Arts and Humanities, English Literature Department. Lee-Ann holds a Bachelor of Arts degree and an Honours degree in English Literature from the University of the Western Cape (UWC).